2015
DOI: 10.1002/pbc.25887
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and Adolescents’ Preferences for Intensified or Reduced Treatment in Randomized Lymphoblastic Leukemia Trials

Abstract: Parents' and adolescents' divergent inclinations toward intensified or reduced therapy emphasize the necessity of actively involving adolescents in the informed consent process, which should also address motives for trial participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…coli- derived ASNases. Unfortunately, ASNase-based therapy has some limitations: (i) pancreas, liver and immune system impairment, (ii) high immunogenicity, (iii) low efficacy and higher toxicity in adult patients, and (iv) low stability in vivo 3 , 4 . In fact, both native proteins are characterized by low in vivo stability, resulting in short half-life and need for several administrations.…”
Section: Introductionmentioning
confidence: 99%
“…coli- derived ASNases. Unfortunately, ASNase-based therapy has some limitations: (i) pancreas, liver and immune system impairment, (ii) high immunogenicity, (iii) low efficacy and higher toxicity in adult patients, and (iv) low stability in vivo 3 , 4 . In fact, both native proteins are characterized by low in vivo stability, resulting in short half-life and need for several administrations.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, collaborative decision-making is only used if parents agree with their adolescent's preferences and the autonomy of the adolescent could potentially be limited-at least in situations where an adolescent wishes to enter a trial, but the parents disagree. In this study, all parents and children had been in agreement, but it is not inconceivable that disagreements in the adolescent-parent dyad can occur, especially in light of the results of our prior study (Tulstrup et al, 2016).…”
Section: Discussionmentioning
confidence: 53%
“…We recently showed that in the NOPHO ALL2000 and ALL2008 randomized trials with paediatric acute lymphoblastic leukaemia (ALL), conducted by the Nordic Society of Paediatric Haematology and Oncology (NOPHO), adolescents were less likely to enrol in an intensification trial and more likely to enrol in a treatment reduction trial. The opposite was the case for younger children, where parents are primary decision‐makers (Tulstrup et al., ). However, it remained uncertain whether these divergent inclinations reflected that parents of children and parents of adolescents had different preferences for either intensified or reduced treatment intensity, or that adolescents had a preference for reduced treatment intensity.…”
Section: Introductionmentioning
confidence: 99%
“…An important limitation of this study is the lack of power, as the trial did not reach the prespecified sample size due to a higher-than-expected parent/patient refusal rate. 14 The premature termination of the study reflected an interim analysis for the Data and Safety Monitoring Committee which indicated that inclusion of the remaining 226 patients to reach the prespecified target was very unlikely to yield a significant difference in EFS.…”
Section: Discussionmentioning
confidence: 99%